Izzivi vodenja osnovne šole - Cencič, Majda (Vodenje v vzgoji in izobraževanju, 2014)
Student groups in schools under headteachers' leadership are very varied, so social inclusion is widely discussed, while the inclusivity of the physical (built) school environment often takes a back seat in professional discussions. Therefore this paper focuses precisely on this physical learning environment and its adaptations for an inclusive education. We were interested to learn what student groups, in headteachers' opinion, are the most numerous and what modifications of the physical learning environment are targeted at various student groups. On the basis of an online questionnaire to which 150 of Slovenia's elementary school headteachers have replied and which has been processed especially in terms of descriptive statistics, replies were obtained stating that, in addition to special needs students, it is the gifted students that are the most numerous in elementary schools. The adaptations of the physical environment are likewise oriented especially toward the special needs children. The findings of the study are then supplemented with suggestions for arranging the physical learning spaces, inside and outside, according to various student needs.
Keywords: elementary schools; headteachers; inclusion; inkluzija; learning environment; osnovne šole; ravnatelji; učenci s posebnimi potrebami; učno okolje; vodenje